Eocene to Miocene paleoclimate reconstruction of the northern Tibetan Plateau: constraints from mineralogy, carbon and oxygen isotopes of lacustrine carbonates in the western Qaidam Basin - Li, Shien; Liu, Peixian; Guan, Ping; Zhang, Daowei; Xia, Xiaomin; Ding, Xiaonan; Zhang, Chi; Zhang, Jihua; Tang, Jianzhou (Frontiers in Earth Science, 2023)
The Cenozoic climatic evolution of the Tibetan Plateau (TP), together with its driving mechanism, have been a subject of interest for decades. This study presents detailed sedimentology, mineralogical (XRD), carbon, and oxygen isotope analyses of lacustrine deposits from the Eocene to the Miocene in the western Qaidam Basin, the northern TP. The petrological observation and XRD data of 109 samples reveal that the sediments are composed of mixed siliciclastic, carbonate, and evaporate minerals. And the carbonate isotopic results show negative δ13C (-7.49‰ to -3.41‰) and negative to slightly positive δ18O values (-14.65‰ to 0.2‰). Both isotopes display a positive correlation with the contents of carbonates and evaporates, which suggests that evaporation is the major controlling factor of carbon and oxygen isotope. Therefore, the isotopes can be used as reliable indicators of the intensity of evaporation for paleoclimatic reconstruction. The reconstruction results reveal three distinct arid stages: top of the lower Xiaganchaigou Formation to the upper Xiaganchaigou Formation (ca.40-32 Ma), bottom of the Xiayoushashan Formation(ca.22-20 Ma), top of the Shangyoushashan Formation (ca.13-8.2 Ma). We suggest that the aridity during ~40-32 Ma may have been related to the regression of the Paratethys Sea and uplift of the TP, while the aridity during 22-20 Ma may have been caused by the uplift and denudation of the mountains around the basin. The aridity after ~13 Ma could be attributed to both global cooling and tectonic events in the northern TP. Furthermore, by comparing the climate records of the Qaidam Basin with those of other basins in Central Asia, a regional correlation can be established between different basins during the first and third drought stages.